(untitled) (Studia Prawnicze / The Legal Studies, 2020)
Umowa deweloperska została uregulowana jako pozakodeksowa umowa nazwana. Celem tej regulacji było zapewnienie nabywcy lokalu adekwatnej ochrony prawnej, jakiej nie gwarantowały dotychczasowe regulacje dotyczące umowy przedwstępnej. Pojęcie nabywcy jest szersze niż pojęcie konsumenta – to osoba fizyczna, bez względu na cel zawierania umowy. Jednym z aspektów ochrony nabywcy jest regulacja przedkontraktowych obowiązków informacyjnych dewelopera. Deweloper zobowiązany jest przed zawarciem umowy poinformować nabywcę o jego sytuacji prawno-finansowej oraz przedstawić szczegóły dotyczące nabywanego lokalu. Przekazane informacje muszą być prawdziwe i rzetelne. Konsekwencje naruszenia obowiązków przedkontraktowych są uzależnione od tego, czy doszło do zawarcia umowy deweloperskiej. Mogą być nimi naprawienie szkody, jaką nabywca poniósł przez to, że liczył na zawarcie umowy; odstąpienie od umowy; uchylenie się od skutków oświadczenia woli; sankcje administracyjne oraz karne. Developer agreements haves been regulated beyond the Polish Civil Code, as a named contract. The necessity to of granting the effective protection to the buyer has been the reason for this regulation, taking into consideration that the a preliminary agreement does not guarantee this protection effectively. The notion of the term “the buyer” has the wider scope than “the consumer” – the buyer means the a natural person, both a he consumer and the an entrepreneur as well, regardless the purpose of concluding the contract. The precontractual informative duties of the developer constitute the one of the aspects of the buyer protection. Before the conclusion of the contract, the developer is obliged to provide the buyer with the information on its financial and legal position, as well as the details concerning the premises to be acquired premises. The aforementioned information hasve to be real and honest. The consequences of the a breach of precontractual duties are various, taking into consideration if the contract hasve been subsequently concluded – the damage repair of the position as the buyer counted on at conclusion of the contract, the withdrawal from the contract, the evasion of the legal consequences of a declaration of intent, as well as the administrative and penal sanctions.